Pengembangan Buku Ajar Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan bagi Siswa Sekolah Dasar / Development of Health and Sports Physical Education Coursebooks for Elementary School Students - Zainul Arifin (Al-Mudarris: Journal Of Education, 2023)
The purpose of this development research is to compile a physical education, sport, and health textbook for grade ten students in the first semester of SDI Salafiyah. The method applied for this research is development research. The data collecting employs questionnaires for experts and students. With the following qualifications: an expert of instructional media and two experts of learnings of physical education, sport, and health; trials for students are conducted through phase I (small group) consisting of 8 students and phase II (big group) consisting of 21 students. The result of the research is as follows: The expert of media reveals that the percentage of evaluation result from the expert of instructional media is 79.95%; the experts of learnings reveals that the average percentage of evaluation result from two experts of learnings is 85.60%; the researcher finds that the overall average percentage as the result of phase I trial (small group) is 87.70%, the researcher also finds that the overall average percentage as the result of phase II trial (big group) is 88.75%. The conclusion of this research reveals that this physical education, sport, and health textbook is perfect with Good criteria, thus it is applicable as an instructional media for students and teachers.